CUBIC GRAF METRIC DIMENSIONS OF CERTAIN - HANTORO, PUDJO
Slater (1975) and Harary & Melter (1976) independently introduced the concept of resolving set and metric dimension of a graph. Let G = (V,E) be a connected graph. We show that dim(G3) = 3 if the order of G3 is a multiple of 4, otherwise dim(G3) = 4. We also give some resolving sets for this graph.